Edukacja środowiskowa młodzieży na przykładzie programów nauczania religii rzymskokatolickiej - Zellma, Anna (Poznańskie Studia Teologiczne, 2014)
A contemporary young man witnesses the continuous strengthening of the relations and the integration between states, communities and cultures. He participates in the processes of globalization and the notions such as national state and “small homelands” are becoming obsolete. Considering the above, systematic environmental education of the young generation by all teachers, including religion teachers, seems essential. The analyses undertaken in the article seek answers to the question of the scope of environmental education in teaching religion to the youth. The following issues are discussed in more detail: definition of environmental education, environmental education program framework in teaching religion to youth, methods of environmental education included in religion lessons. Reference is made to the religion teaching curriculum in Polish schools. New educational challenges are also indicated.